The admissible contents of experience - Hawley, Katherine (Katherine Jane); Macpherson, Fiona (Chichester, West Sussex, UK ; Malden, MA : Wiley-Blackwell, 2011)
"Which objects and properties are represented in perceptual experience? Although perceptual experiences frequently give rise to beliefs, the content of these beliefs do not always simply reflect the contents of the experiences on which they are based. Instead, they often rest on background knowledge and beliefs, as well as experience. This raises the question of how are we able to determine what the admissible contents of experience are, whether they include singular or existential contents, and whether they include contents pertaining to causation or natural kinds. The papers in this collection address these issues, together with questions concerning the nature of perceptual content. They deal with the central issues of whether perceptual content is similar to the content of the propositional attitudes; whether all states with content fall neatly into the categories of either belief or experience. The book also focuses on whether there exists a continuum from states that are more like perceptual experiences to states that are more like belief, and, indeed, ultimately whether we should consider perceptual experiences to have content at all. This ground-breaking volume is published in association with the journal Philosophical Quarterly"--
Machine generated contents note: Introduction (Katherine Hawley, University of St. Andrews and Fiona Macpherson, University of Glasgow). -- 1. Perception And The Reach Of Phenomenal Content (Tim Bayne, University of Oxford). -- 2. Seeing Causings And Hearing Gestures (Steven Butterfill, University of Warwick). -- 3. Experience And Content (Alex Byrne, Massachusetts Institute of Technology). -- 4. Is Perception A Propositional Attitude? (Tim Crane, University College London). -- 5. Conscious Reference (Alva Noë, University of California, Berkeley). -- 6. What Are The Contents Of Experiences? (Adam Pautz, University of Texas at Austin). -- 7. Aspect-Switching And Visual Phenomenal Character (Richard Price, University of Oxford). -- 8. The Visual Experience Of Causation (Susanna Siegel, Harvard University). -- 9. The Admissible Contents Of Visual Experience (Michael Tye, University of Texas at Austin).
Includes bibliographical references and index.
Keywords: Experience; Perception; Evidence; Belief and doubt; PHILOSOPHY / Logic